2015
DOI: 10.3233/bme-151557
|View full text |Cite
|
Sign up to set email alerts
|

Influence of viscoelastic properties of an hyaluronic acid-based hydrogel on viability of mesenchymal stem cells

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. Abstract. BACKGROUND:The present research is involved in the framework of the biotherapy using mesenchymal stem cells (MSCs). Here, MSC encapsulation in a hydrogel based on hyaluronic acid (HA) is investigated to optimize the composition of the biomaterial. METHODS: Several formulations candidates of the hydrogel (9 in total) are postulated as a scaffold for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The viscoelastic properties of hydrogels are an integral result of individual characteristics and interactions of the structural component of a material (for example, fibers or filaments), chemical (for example, ionic bonds), fluid and cells [[12], [13], [14]]. There is no doubt that the viscoelastic properties of both artificial and natural ECMs directly affect cell migration, proliferation and differentiation [[15], [16], [17]]. For example, O. Chaudhuri et al (2016) found out that cells'spreading, proliferation, and osteogenic differentiation of mesenchymal stem cells (MSCs) are all enhanced in cells cultured in gels with faster relaxation [18].…”
Section: Introductionmentioning
confidence: 99%
“…The viscoelastic properties of hydrogels are an integral result of individual characteristics and interactions of the structural component of a material (for example, fibers or filaments), chemical (for example, ionic bonds), fluid and cells [[12], [13], [14]]. There is no doubt that the viscoelastic properties of both artificial and natural ECMs directly affect cell migration, proliferation and differentiation [[15], [16], [17]]. For example, O. Chaudhuri et al (2016) found out that cells'spreading, proliferation, and osteogenic differentiation of mesenchymal stem cells (MSCs) are all enhanced in cells cultured in gels with faster relaxation [18].…”
Section: Introductionmentioning
confidence: 99%
“…• can change viscosity depending on modification 121,137 • can affect hydrophobicity of hydrogel 167,170 incorporate interpenetrating/semiinterpenetrating networks…”
Section: Acs Biomaterials Science and Engineeringmentioning
confidence: 99%
“…137 Variation of viscoelastic properties in this way influences mesenchymal stem cell (MSC) viability. 121 More recently, Lou et al employed a dynamic hydrazone bond to cross-link HA polymers within an interpenetrating network of HA and collagen I in order to confer stress relaxation to the hydrogel. Varying the crosslinker affinity, MW of HA, and concentration of HA allowed for tuning of the relaxation time, with faster relaxation times promoting MSC spreading and focal adhesion formation.…”
Section: Incorporation Of Ha Biophysical Properties Into Biomaterials...mentioning
confidence: 99%
See 1 more Smart Citation
“…HA is a non-sulfated glycosaminoglycan (GAG) in cartilaginous ECM maintaining chondrocyte functions and a component of synovial fluid responsible for its viscoelasticy [ 3 ]. In vitro studies revealed that HA modulates inflammation inhibiting matrix metalloproteinases (MMPs) [ 77 ]. HA has potential biological effects, including the enhancement of the chondrogenic effects of MSCs [ 78 ] and the promotion of synovial cell or chondrocyte migration in the presence of basic fibroblast growth factors [ 79 ].…”
Section: Discussionmentioning
confidence: 99%